Piloting a Safe Health Researcher course - Corti, Louise; Wiltshire, Deborah (International Journal of Population Data Science, 2019)
Robust and standardised licensing and governance frameworks are used to ensure that datasets intended for research use are made available under the terms and conditions specified by a data owner. The UK Data Service makes use of the Five Safes framework to operate its 3-tier data access policy, and ensuring that data classified as personal data can be made available via appropriate legal gateways. This set of principles has gained traction with national statistics around the world, yet it is remarkably absent in the narrative of data access for health research. The health domain tends to focus on ‘data sharing agreements’, and less on training around trust, security and disclosure. The concept of a Safe Health Researcher is missing, yet is appealing. The UK Data Service has been piloting such a half day course, with colleagues in the health domain. The training helps consolidate the less well defined idea of a ‘bona fide’ researcher, typically required by funders such as the UK’s Medical Research Council when accessing their data assets. The term bonafide makes some assumptions about the credentials of the researchers, yet fails to ‘test’ them, instead relying on ‘trust ‘underwritten by the individual’s university, and maybe a short online security course. While purposeful breaches are certainly not common place, a researcher accessing personal or sensitive data would benefit from a structured half-day course that covers aspects of: potential/ actual disclosure risk in health data and appropriate access pathways; safeguards to be put in place when data with risk are shared; and what might constitute a published ‘unsafe’ output, i.e. with a risk of disclosure. The training focuses on health data and research examples, and draws on aspects of the research data management and publishing training undertaken by the UK Data Service (e.g. Corti et al, 2014) and on the UK Statistics Authority approved ‘Safe Research Training’ (SRT) course, which leads to the Accredited Researcher status.